2023
DOI: 10.1002/jsfa.13057
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus fermentum HF06‐derived paraprobiotic and postbiotic alleviate intestinal barrier damage and gut microbiota disruption in mice with ulcerative colitis

Chunhong Liu,
Xiaofen Qi,
Dan Li
et al.

Abstract: BACKGROUNDParaprobiotics and postbiotics have shown potential in the treatment of ulcerative colitis (UC). However, their in vivo application is still in its infancy and their mechanisms of action are not well understood.RESULTSHere, we investigated the mitigation effects of the Limosilactobacillus fermentum HF06 derived paraprobiotic (6‐PA) and postbiotic (6‐PS) on dextran sulfate sodium (DSS) induced UC and the potential mechanisms. Results indicated that the administration of 6‐PA and 6‐PS resulted in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 66 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…It refers to preparations of inanimate microorganisms and/or their components that are beneficial to the health of the host ( Salminen et al, 2021 ). Recent studies have shown that postbiotics show potential in the treatment of UC, with some studies claiming that probiotics and postbiotics have similar abilities to improve disease phenotypes ( Liu et al, 2023 ). For example, a preclinical study found that Lactobacillus plantarum -derived postbiotics were able to optimize the composition of the intestinal flora and significantly modulate the levels of short-chain fatty acids and neuroactive molecules (5-hydroxytryptamine, γ-aminobutyric acid) in vivo , which in turn ameliorated Salmonella -induced neurological dysfunction ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It refers to preparations of inanimate microorganisms and/or their components that are beneficial to the health of the host ( Salminen et al, 2021 ). Recent studies have shown that postbiotics show potential in the treatment of UC, with some studies claiming that probiotics and postbiotics have similar abilities to improve disease phenotypes ( Liu et al, 2023 ). For example, a preclinical study found that Lactobacillus plantarum -derived postbiotics were able to optimize the composition of the intestinal flora and significantly modulate the levels of short-chain fatty acids and neuroactive molecules (5-hydroxytryptamine, γ-aminobutyric acid) in vivo , which in turn ameliorated Salmonella -induced neurological dysfunction ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%